Salt-Tolerant Plants, Halophytes, as Renewable Natural Resources for Cancer Prevention and Treatment: Roles of Phenolics and Flavonoids in Immunomodulation and Suppression of Oxidative Stress towards Cancer Management - Mohammed, Hamdoon A.; Emwas, Abdul-Hamid; Khan, Riaz A. (International journal of molecular sciences, 2023)
Halophytes and xerophytes, plants with adequate tolerance to high salinity with strong ability to survive in drought ecosystem, have been recognized for their nutritional and medicinal values owing to their comparatively higher productions of secondary metabolites, primarily the phenolics, and the flavonoids, as compared to the normal vegetation in other climatic regions. Given the consistent increases in desertification around the world, which are associated with increasing salinity, high temperature, and water scarcity, the survival of halophytes due to their secondary metabolic contents has prioritized these plant species, which have now become increasingly important for environmental protection, land reclamation, and food and animal-feed security, with their primary utility in traditional societies as sources of drugs. On the medicinal herbs front, because the fight against cancer is still ongoing, there is an urgent need for development of more efficient, safe, and novel chemotherapeutic agents, than those currently available. The current review describes these plants and their secondary-metabolite-based chemical products as promising candidates for developing newer cancer therapeutics. It further discusses the prophylactic roles of these plants, and their constituents in prevention and management of cancers, through an exploration of their phytochemical and pharmacological properties, with a view on immunomodulation. The important roles of various phenolics and structurally diverse flavonoids as major constituents of the halophytes in suppressing oxidative stress, immunomodulation, and anti-cancer effects are the subject matter of this review and these aspects are outlined in details.